Shifting Values and Practices of Customary Inheritance Law in Indonesia's Multicultural Society - Janeko, Janeko; janeko (Darajatuna: Interdisciplinary Journal of Islamic Studies, 2025)
The shift in values in the practice of customary inheritance law in Indonesia is an inevitable phenomenon along with social, economic, and cultural developments in multicultural societies. Customary inheritance law, which was initially based on the principles of kinship, deliberation, and social balance, now faces challenges due to the entry of modern values, national law, and religious influences. This study aims to analyze the dynamics of these value shifts, the factors that drive change, and their implications for the social order of indigenous peoples. The research method used is a juridical-sociological approach with literature study. The results of the study show that the shift in the value of customary inheritance law is more influenced by modernization, urbanization, and awareness of gender equality. This shift has a positive impact in the form of growing the value of justice and the protection of women's rights, but it also has negative impacts such as weakening social cohesion and the fading of cultural identity. Thus, a strategy of reconstruction of customary inheritance law that is adaptive to the development of the times, without eliminating the values of local wisdom that are the main foundation of customary law.